An Analysis of Students’ Science Process Skills at Muhammadiyah 1 Berbah Junior High School - Rusdiman Buhera; Rizky Merian Muspa (Saqbe: Jurnal Sains dan Pembelajarannya, 2026)
This quantitative descriptive research, a preliminary study, examined science process skills among 193 eighth and ninth-grade students at Muhammadiyah 1 Berbah Junior High School, addressing the limited comprehensive assessments of these fundamental skills in Indonesia. Using a previously validated research instrument that assessed eight skill indicators through multiple-choice questions, findings revealed varied proficiency levels: observation scored lowest (18, very low), prediction (33), and classification (35) showed low levels while experimenting (48), data interpretation (45), concept application (50), and communication (45) demonstrated medium proficiency, with hypothesis formulation scoring highest (69); the overall average score was 43 (medium level), with concerning student distribution across proficiency categories (8% very high, 20% high, 15% medium, 41% low, 17% very low). With 58% of students performing below medium level, results indicate an urgent need for instructional interventions targeting science process skills development. These provide critical baseline data for curriculum development and instructional reforms, particularly emphasizing inquiry-based approaches to address deficiencies in observation, prediction, and classification skills.